Diagnóstico e identificação arquivística como subsídios para gestão documental: o Programa de Pós-Graduação em Direito da UFPA - OLIVEIRA, Adriana Couto Santiago de (2018)
This research had as purpose to present the importance of the diagnosis and propose a model of identification form of documentary typology for the Postgraduate Program in Law at the Federal University of Pará as a proposal to deal with the accumulated documentary mass and without identification of its file, applying the diagnosis which is used as one of the first steps in the technical treatment for the accumulated documentary mass and demonstrating the importance of this technical procedure as the need to perform the identification of documents based on the work of the professional Archivist. The characteristic of this research is empirical, because it uses the case study method based on an exploratory and qualitative approach and participatory observation. The elaboration of this work constitutes a theoretical foundation which seeks to verify concepts of Archival Identification and Diagnosis in Brazil, by analyzing the procedures and techniques of Documentary Management aiming to elaborate a model of Archival Identification. The result of the research indicates the peculiarities of the program, the collection, the construction of a form which was applied to justify the relevance of the function of Archival Identification as a technique to handle the documentation of the accumulated documentary mass.